Rethinking precariousness and its evolution: A four-country study of work in food retail. (December 2019) - O'Brady, Sean
This article analyses the expansion of precarious work in industrialized economies, integrating the welfare regime, risk shift and segmentation literatures. I examine trends in wages, working hours, pensions and healthcare in food retail in Canada, Germany, Sweden and the USA between 1980 and 2016. Precariousness increased in each country, but the form and degree of change differed markedly, reflecting the effects of product market competition, bargaining centralization and labour regulation.